APLIKASI TIK TOK SEBAGAI MEDIA PEMBELAJARAN MAHARAH KALAM - Miftachul Taubah; Muhammad Nur Hadi (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
This article is a written idea related to the development of learning media. Along with the adoption of the 4.0 industrial revolution era, the dynamics of learning should also follow it by starting to reduce the use of conventional learning media and starting to switch to modern learning media. Learning media in the digital era must be aligned with technological developments. Learning media must be interesting, close and interactive with students. The Tik Tok application comes with a negative impression from the community, but ironically, the average millennial generation really enjoys this application. Based on the premise of these facts, a middle ground generalization can be drawn that the Tik Tok application will be an interesting and fun learning medium if it is processed and used appropriately. Through the tik tok application, an educator can create interactive learning and in accordance with the situations and conditions of students and be able to adapt to the times.